Substance use patterns of hospitalized adolescent inhalant users: a comparison according to gender and place of residence - Ögel, Kültegin; Taner, Sevil; Tosun, Musa; Tamar Gürol, Defne; Liman, Olcay (Journal of Dependence, 2005)
Objective: The objective of this research is to compare the substance use patterns of hospitalized adolescent inhalant users under 18 according to gender and place of residence.Method: A face-to-face interview questionnaire which was developed by the researchers was applied to 209 adolescent inhalant users who were inpatients at the Inhalant Use Research and Treatment Center (UMATEM) between 2002-2003.Results: All of the subjects reported using paint thinner and glue. The prevalence of glue use was higher compared to paint thinner and was significantly higher for females compared to males and those living with their family compared to those living in the street. No significant difference was found between those living in the street and those living with their family in terms of using inhalants on the street and within a group, getting medical help, and trying to stop using inhalants. The rate of starting to use inhalants within a group was higher among those living in the street. The rates of using inhalants in the street and trying to stop using inhalants were higher for males compared to females.Average age of onset of inhalant use was approximately 12. Average age of onset of inhalant use was younger for those living in the street compared to those living with their family. There was no difference between genders in terms of the average age of onset of inhalant use.Most prevalent substances used together with inhalants were tobacco, alcohol, marijuana and flunitrazepam. The risk for using alcohol and flunitrazepam was higher for those living in the street compared to those living with their family. Among male inhalant users the risk for marijuana use was the highest while for female inhalant users the risk for biperiden and heroin use were higher.The risk for meeting more than three dependence criterion was three times higher for those living in the street compared to those living with their family.
Keywords: Inhalant; inhalant use; street children; gender; residence; addiction